Complications of Influenza A or B Virus Infection in Individuals With SCN1A-Positive Dravet Syndrome. (24th January 2023) - Howell, Katherine B.; Butcher, Sophie; Schneider, Amy L.; Russ-Hall, Sophie; Muzariri, Pearl R.; Kerr, Rachel; Overmars, Isabella; Hayman, Michael; Kornberg, Andrew J.; Danchin, Margie; Crawford, Nigel W.; Scheffer, Ingrid E.
Abstract : Background and Objectives: To determine the frequency and spectrum of complications of influenza infection in individuals with SCN1A -positive Dravet syndrome ( SCN1A -DS). Methods: Individuals with SCN1A -DS were identified in neurologists' care at 2 hospitals in Melbourne, Australia, with additional searches of EEG databases, the Victorian PAEDS FluCan influenza database, and the University of Melbourne Epilepsy Genetics Research Program database. Medical records were searched and families questioned to identify individuals who had an influenza infection; reported infections were confirmed by pathology report. For these individuals, we obtained baseline clinical characteristics and clinical details of the influenza infection. Results: Twenty-one of 82 individuals (26%) had 24 documented influenza infections (17 influenza A and 7 influenza B) at age 0.5–25 years (median 4 years). All presented to hospital, 18/24 (75%) for status epilepticus or seizure exacerbations. Recovery was prompt in 18/24 (75%) infections, delayed but complete in 1/24 (4%) and incomplete in 5/24 (21%). One child died from influenza pneumonia, and long-term neurologic sequelae were seen with 4 infections. These individuals were poorly responsive after termination of status epilepticus. Brain imaging in 2 showed cerebral edema and 1 also having imaging features of laminar necrosis. All have ongoing neurologic deficits compared with their baseline, 1 having profound global impairment. Discussion: Our data show that patients with SCN1A -DS are highly susceptible to neurologic complications during and severe sequelae after influenza infection, including moderate to severe persistent neurologic impairments and death. Safe administration of the seasonal influenza vaccine should be prioritized for this population.